Research of the Potential Vaginal Microbiome Biomarkers for High-Grade Squamous Intraepithelial Lesion - Chao, Xiaopei; Wang, Lan; Wang, Shu; Lang, Jinghe; Tan, Xianjie; Fan, Qingbo; Shi, Honghui (Frontiers in Medicine, 2021)
Vaginal microbiome may have a role in HPV infection and cervical neoplasm. To explore potential vaginal microbiome biomarkers for high-grade squamous intraepithelial lesion (HSIL), and to find the best scheme to facilitate the current cervical cancer screening strategy. This study enrolled 272 women, including 83 confirmed with HSIL, 86 with HPV infection but without cervical neoplasm, and 103 without HPV infection as controls. Vaginal microbiome composition was determined by sequencing of barcoded 16S rDNA gene fragments (V4) on Illumina HiSeq2500. The relative increasing abundance of Stenotrophomonas, Streptococcus, and Pseudomonas, and a concomitant paucity of Dialister, unidentified Prevotellaceae, Faecalibacterium, Bifidobacterium and Bacteroides, were related with HSIL, which can be used to predict the development of HISL in high-risk HPV infected patients. The relative abundance of Stenotrophomonas being over 0.0090387%, or Faecalibacterium being under 0.01420015%, or Bifidobacterium being under 0.0116183% maybe a good predictor for HSIL for those infected with HPV 16 and/or 18. The relative abundance of Stenotrophomonas being over 0.01549105%, or Streptococcus being over 0.48409585%, or Bacteroides being under 0.0296912% maybe a good predictor for HSIL for those infected with the 12 other high-risk types of HPV with concurrent abnormal TCT results. This study revealed that potential vaginal microbiome biomarkers may relate to HSIL, and can facilitate the cervical cancer screening.